Surviving from Child Abuse in novel Sing, Unburied, Sing (2017) by Jesmyn Ward - Khaira, Fanisa; Anwar, Desvalini (Universitas Negeri Padang, 2021)
This research is an analysis of the novel Sing, Unburied, Sing (2017) by Jesmyn Ward. The purpose of this study is to reveal the issue of surviving child abuse in the novel Sing, Unburied, Sing (2017) by Jesmyn Ward. The issue of surviving from child abuse refers to the type of abuse experienced by the character, the impact of the abuse on the character, and the character's efforts to overcome the abuse. This study uses the concept of life instinct by Sigmund Freud. This study uses the text and context contained in the novel. As a result, the character can go through his difficult time and can rise from the abuse he experienced.